Livestock Service through Knowledge of Society: Mainstreaming Contribution of Women Knowledge Holders - R. K, Ravikumar; Dutta, Lopamudra; Bera, Amit; Kumar, Vipin (International Journal of Bio-resource and Stress Management, 2016)
Sustaining farm income through effective, economical, and environment friendly technologies are imminent particularly in tropical countries. Enhanced expectation of people’s aspiration, gap between haves and have-nots, and food security have been a challenge for public/private institutions to address. This gap can be bridged through indigenous knowledge system sustained by creative communities with resilience. However, successful intervention programs of engaging knowledge holders beyond documentation are limited. National Innovation Foundation, Indiahas embarked upon larger research program in West Bengal (India). The primary objective was to generate meaningful evidence for promoting quality livestock health care through women knowledge holders. This is based on the Honey Bee Network philosophy that insists necessity to understand and imbibe values inherited by individual and/or community of knowledge system. The study highlights social capital gained by women knowledge holders which will form key determinant towards optimum utilization of these technologies. A model of incorporating indigenous veterinary medicine for benefit of farming community is illustrated. There is a need of supporting and reorienting veterinary service by public system to utilize and scale-up knowledge of society. Thus the study brings forth contribution of women knowledge holders within their social fabric. The paper articulates significance of social behaviour by conducting network meeting and an approach to engage hitherto less recognized technological alternatives for improvising quality livestock service.